Pharmacokinetic drug evaluation of mepolizumab for the treatment of severe asthma associated with persistent eosinophilic inflammation in adults. (2nd December 2017) - Kallur, Lakshmi; Gonzalez-Estrada, Alexei; Eidelman, Frank; Dimov, Ves
ABSTRACT: Introduction : Mepolizumab is a humanized monoclonal antibody that binds to and inactivates IL-5. It is available as a subcutaneous preparation. The practical application of mepolizumab is as an add-on therapy in the treatment of severe eosinophilic asthma. Areas covered : This article was created from a comprehensive literature search with information taken from meta-analyses, systematic reviews, and clinical trials of adults. The articles that have been selected evaluate the use of mepolizumab and its role in eosinophilic asthma. Expert opinion : Mepolizumab is significantly more effective than placebo in reducing exacerbations and need for systemic corticosteroids in severe eosinophilic asthma. There is a lack of head to head studies comparing mepolizumab to other monoclonal anti-IL-5 inhibitors in severe eosinophilic asthma. Post marketing surveillance revealed risk of anaphylaxis that is below 1%.